rDNA genetic imbalance and nucleolar chromatin restructuring is induced by distant hybridization between Raphanus sativus and Brassica alboglabra. - Hong Long; Chunli Chen; Bing Wang; Yanni Feng (PLoS ONE)
The expression of rDNA in hybrids inherited from only one progenitor refers to nucleolar dominance. The molecular basis for choosing which genes to silence remains unclear. We report genetic imbalance induced by distant hybridization correlates with formation of rDNA genes (NORs) in the hybrids between Raphanus sativus L. and Brassica alboglabra Bailey. Moreover, increased CCGG methylation of rDNA in F1 hybrids is concomitant with Raphanus-derived rDNA gene silencing and rDNA transcriptional inactivity revealed by nucleolar configuration restriction. Newly formed rDNA gene locus occurred through chromosomal in F1 hybrids via chromosomal imbalance. NORs are gained de novo, lost, and/or transposed in the new genome. Inhibition of methyltransferases leads to changes in nucleolar architecture, implicating a key role of methylation in control of nucleolar dominance and vital nucleolar configuration transition. Our findings suggest that gene imbalance and methylation-related chromatin restructuring is important for rDNA gene silencing that may be crucial for synthesis of specific proteins.